Mobilizing Intolerance: Teungku Dayah (Ulama) and Religious Discourse in Aceh, Indonesia - Nasution, Ismail Fahmi Arrauf; Wildan, T.; Anzaikhan, M.; Faidi, Ahmad (Journal of Al-Tamaddun, 2024)
In 2018, Aceh was ranked 32nd in the index of tolerant cities in Indonesia conducted by the Setara Institute. The poor rating of religious tolerance in Aceh was due to an act of violence that occurred in Aceh in the previous periods, in which religious grounds were used. Ironically, this act was carried out by people who claim the authority of the Aswaja ideology in Aceh. The field research seeks to uncover the real root of the problem by interviewing religious authorities in Aceh, namely Teungku Dayah (ulama in Acehnese society), Santri (Muslim Students), and lecturers at Islamic higher education institutions. The results of the study showed that the acts of violence in Aceh stemmed from Teungku Dayah’s inaccurate understanding of pluralism. Pluralism is understood and positioned as an ideology that contradicts and threatens the sustainability of the Aswaja’s ideology in Aceh.